Employing the Question-Answer Relationships Technique to Enhance the Comprehension of Maharah Qiraah Students - Muhammad Afthon Ulin Nuha; Nurul Musyafa’ah (Pascasarjana UM, 2022)
Fifth-grade students at MI Bahrul Ulum Tambakberas Jombang demonstrate low comprehension in Arabic reading, struggling to identify main ideas, form conclusions, and retell narratives in their language. This suggests that their maharah qiraah, or reading proficiency, is underdeveloped. The Question-Answer Relationship (QAR) method provides a structured approach to enhance their reading comprehension by aiding in understanding text, answering questions, and drawing conclusions from the reading material. This study aims to: 1) Assess the level of comprehension before and after implementing the QAR method at MI Bahrul Ulum Tambakberas Jombang, and 2) Evaluate the efficacy of the QAR method in improving the maharah qiraah of the fifth-grade students. Utilizing a quantitative approach with an actual experiment, this research employs purposive sampling for two classes, V-A and V-B. The analytical approach incorporates descriptive research, normality, homogeneity, and hypothesis testing. Findings suggest that post-QAR method intervention, there is a marked improvement in Arabic learning in the experimental class, as evidenced by significant post-test score increases, enhanced ability to form conclusions, interpret complex words in the text, and explain acquired values from the reading. Descriptive analysis results show that the average pretest score in the experimental class was 66, increasing to 76 post-intervention. Conversely, the control class averaged pretest scores of 58, with a minor increase to 62 post-intervention. These results indicate the experimental class's superior performance and significant improvement compared to the control class, demonstrating the effectiveness of the QAR method in Arabic reading comprehension.